Tafsir Bil Maksur and its significance in the interpretation of the Qur'an - Rahma, Cut Dewi; Syabuddin, Syabuddin (JUPE : Jurnal Pendidikan Mandala, 2024)
Tafsir bil-Ma'tsur is a method of interpreting Qur'anic verses using other Qur'anic verses, hadith, the accounts of the companions, and the tabi'in. This tafsir is also known as riwayah tafsir or manqul tafsir, meaning the interpretation of the Qur'an based on the accounts of the companions and tabi'in. This writing aims to explain what is meant by tafsir bil-Ma'tsur and the criteria that must be met to be called tafsir bil-Ma'tsur. The research method used is qualitative descriptive with a literature review. The results of the study show that tafsir bil-Ma'tsur includes interpreting the Qur'an with the Qur'an, the Sunnah, and the sayings (qaul) of the companions. If the interpretation is done by the companions, it is called tafsir sahabat. If done by the tabi'in, it is called tafsir tabi'in. This study finds that tafsir bil-Ma'tsur is a method of interpreting the Qur'an using various reliable sources, ensuring a deep and accurate understanding of the Qur'anic text.